2021
DOI: 10.1101/2021.05.17.444505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toughening mechanisms for the attachment of architectured materials: The mechanics of the tendon enthesis

Abstract: Architectured materials offer tailored mechanical properties but are limited in engineering applications due to challenges in maintaining toughness across their attachments. The enthesis connects tendon and bone, two vastly different architectured materials, and exhibits toughness across a wide range of loadings. Understanding the mechanisms by which this is achieved could inform the development of engineered attachments. Integrating experiments, simulations, and novel imaging that enabled simultaneous observa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…50 Thus, in our study, the strain likely deviated to the weakest area of the sample, leading to failure within the bone. This observation is in line with the avulsion fractures described by Deymier et al ( 2019) and Golman et al (2021) 51 at the supraspinatus tendon insertion following monotonic uniaxial tensile loading in mice, where the supraspinatus muscle had been paralyzed by treatment with botulinum toxin. In the latter study, in contrast to our study, it has been reported a decreased maximum load in response to unloading, positively correlated with a decrease in bone architectural parameters, such as trabecular and cortical thicknesses, BV/TV, or bone mineral density.…”
Section: Discussionsupporting
confidence: 89%
“…50 Thus, in our study, the strain likely deviated to the weakest area of the sample, leading to failure within the bone. This observation is in line with the avulsion fractures described by Deymier et al ( 2019) and Golman et al (2021) 51 at the supraspinatus tendon insertion following monotonic uniaxial tensile loading in mice, where the supraspinatus muscle had been paralyzed by treatment with botulinum toxin. In the latter study, in contrast to our study, it has been reported a decreased maximum load in response to unloading, positively correlated with a decrease in bone architectural parameters, such as trabecular and cortical thicknesses, BV/TV, or bone mineral density.…”
Section: Discussionsupporting
confidence: 89%
“…Others have also shown that disruption of the mineral matrix can significantly reduce the tensile strength of the enthesis. 28,29 Surprisingly, despite the thinner mineral thickness at the adult supraspinatus and Achilles entheses, Fgf9 ScxCre mice had increased cellular density at the attachment site. Previously, increased mesenchymal cellularity has been linked to the delayed palatal growth in embryos with global deletion of Fgf9.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also shown that disruption of the mineral matrix can significantly reduce the tensile strength of the enthesis. 31,32 Surprisingly, despite the thinner mineralized bone at the adult supraspinatus and Achilles entheses, Fgf9 ScxCre mice had increased cellular density at the attachment site. Previously, increased mesenchymal cellularity has been linked to the delayed palatal growth in embryos with global deletion of Fgf9 .…”
Section: Discussionmentioning
confidence: 99%